Lesotho - HIV Prevention Response and Modes of Transmission Analysis - World Bank (World Bank, 2012)
The purpose of this modes of transmission (MoT) study is 'to contribute to the ongoing efforts to understand the epidemic and response in Lesotho and thus help the country improve the scope (doing the right kind of activities), relevance (with the right populations), and comprehensiveness (reaching all members of target populations) of Human Immunodeficiency Virus (HIV) prevention efforts'. The process for the Know Your Epidemic (KYE) was an in-depth review of available epidemiological data from Lesotho and the sub-region, and application of the UNAIDS incidence estimation model. The aim was to determine the epidemiology of new (incident) infections. For the Know Your Response (KYR) part, data were collected on the policy context for prevention and on implemented prevention activities and programs. Prevention-specific data from the National AIDS Spending Assessment (NASA) of 2008 and previous two years were reviewed. In a final step, the KYE and KYR evidence was linked to produce an epidemic, response and policy synthesis with recommendations to improve HIV prevention in Lesotho through aligning prevention activities with the evidence on the sources of new infections. The study examined the hypothesis that multiple longer-term partnerships between single young people as well as between married or cohabiting adults are the major driver of HIV transmission, happening in a context of relaxed social norms regarding multiple partners and low risk perception. The findings confirmed this hypothesis -- sexual concurrency is exceptionally high in Lesotho; multiple sexual relationships before and during marriage, together with low levels of full male circumcision are major risk factors in Lesotho's hyper endemic HIV situation.